Model Kurikulum Fullday School dengan Sistem Terpadu di Sekolah Dasar (SD) Islam Terpadu Cordova Samarinda - Kadi, Titi (SYAMIL, 2015)
The appearance phenomenon of Integrated Islamic Elementary School (IIES) that recently sponsored by Jaringan Sekolah Islam Terpadu (JSIT) in the middle of merger trend of Elementary schools which are lack of student is interesting to observe. One of the Integrated Islamic Elementary School in Samarinda which applied the curriculum concept with full day school system is the Integrated Islamic Elemantary School of Cordova Samarinda. Cordova itself taken from the famous University name in the Turkish reign of Usmani, which the education of Muslim was growing faster at that time. Curriculum and learning in IIES of Cordova integrate the general learning with the religion learning equally, even they also add the Islamic values into all general learning subjectÂ  without decreasing the quality of learning value. The aim of this research are to observe: a) the curriculum model of full day school with integrated system in Integrated Islamic Elementary School of Cordova Samarinda, b) the curriculum development model of full day school with integrated system in Integrated Islamic Elementary School of Cordova Samarinda, c) the implementation of the curriculum model of full day school with integrated system in Integrated Islamic Elementary School of Cordova Samarinda is. This research utilizes the qualitative approach, where the data collecting technique used were observation, in depth interview, and document study. The analysis technique used was non statistic, which done by analyzing through the description of words or sentences in the form of explanation for the conclusion. In analyzing the data, the researcher used phasing which are as follows : (a) analyzing the data from all sources, (b) reducing the data, (c) arranging the data in units, (d) categorizing while conducting the coding, (e) checking the data validity. The finding of this research can be presented as follows : Curriculum model in IIES of Cordova is the integrated curriculum between KTSP, JSIT, character education, and local curriculum. Curriculum development model in IIES of Cordova Samarinda has the support of the stakeholders which called the âgrass roots systemâ approach. The steps are (a) make the development group of KTSP in the school, (b) held the FGD between the development group and the stakeholders, (c) make the KTSP draft, (d) the school principle or the vice of curriculum need to make the validity to the school committee, and draft legalization to the education board, (e) the supervised KTSP draft has been through the process of validation and legalization, KTSP document is implementative for the school. Curriculum implementation model in IIES of Cordova Samarinda consists of the parenting integration : formal, nonformal, and informal design. Material integration : religion, general, talent and interest, also life skill. Field integration : cognitive, affective, and psychomotor. Process integration are learning and hidden curriculum.